ANALISIS KEMAMPUAN HISTORICAL COMPREHENSION SISWA PADA MATERI INDONESIA MERDEKA (DARI RENGASDENGKLOK HINGGA PEGANGSAAN TIMUR) DI MADRASAH ALIYAH NEGERI 1 LAMPUNG TIMUR - Muhammad Irawan; Umi Hartati (UNIVERSITAS MUHAMMADIYAH METRO, 2018)
Historical understanding needs to be owned by everyone from an early age in order to know and understand the meaning of past events so that they can be used as a basis for attitudes in facing the present reality and determining the future. Based on the results of the pre-survey conducted at Madrasah Aliyah Negeri 1 East Lampung in the academic year of 2017/2018, the ability of Historical Comprehension students to know the purpose of this study is to determine the ability of Historical Comprehension of students of MAN 1 East Lampung in the material from Regasdengklok to Pegangsaan Timur. Discussed the results of the study 48 students of Madrasah Aliyah Negeri 1 East Lampung, it can be described that the number of true scores of students from each item item is 986 and the average value is 20.54, the measured aspect is (C2) understanding obtained 10% of participants have a very high ability in understanding history, 33% of students have a high ability to understand history, 12.5% of students have moderate historical comprehension abilities, 37% of students have a low historical understanding, and 6.2% of students have historical understanding is very lacking, if the total students who have a historical understanding of 56.25% while those who have not% have a historical understanding of 43.75% of the factors of students who have the ability to understand history, namely, high interest, high motivation, positive attitude when learning and the maximum utilization of learning resources by students, while those who do not have the ability to understand history are interests re well, low motivation, negative attitude and utilization of learning resources that are less than optimal.